The influence of price perception, product quality, and promotion on purchasing decisions for betawi nasi ulam - Suryani Chodidjah (Institute of Computer Science (IOCS), 2026)
This study examines the influence of price perception, product quality, and promotion on purchasing decisions regarding Nasi Ulam Betawi. Traditional culinary dishes face increasingly stiff competition from modern food products, particularly among young urban consumers. A quantitative explanatory research was employed, utilizing primary data collected directly from respondents via structured questionnaires. Purposive sampling was used to select a sample of 155 respondents who had previously purchased and consumed Nasi Ulam Betawi. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS software, encompassing analyses of outer loadings, discriminant validity, multicollinearity, the coefficient of determination, and hypothesis testing procedures. The results indicate that price perception, product quality, and promotion each exert a positive and statistically significant influence on purchasing decisions; this is evidenced by p-values ??of 0.002 for the influence of product quality and price perception on purchasing decisions, and 0.000 for promotion. Promotion demonstrated the strongest influence, followed by price perception and product quality, which showed equal levels of impact, along with an R² value of 80.1%. The path coefficient values ??from the original sample indicate a positive and strong influence Price Perception 0.294, Product Quality 0.306, and Promotion 0.363. The study concludes that businesses in the traditional culinary sector need to strengthen promotional strategies, maintain competitive and fair pricing, and consistently improve product quality to sustain consumer interest and support the preservation of Betawi culinary heritage